2020
DOI: 10.1007/s12029-020-00518-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Helicobacter pylori-Induced Gastric Cancer

Abstract: Introduction Various types of cancers threaten human life. The role of bacteria in causing cancer is controversial, but it has been determined that the Helicobacter pylori infection is one of the identified risk factors for gastric cancer. Helicobacter pylori infection is highly prevalent, and about half of the world , s population is infected with it. Objective The aim of this study was the role of Helicobacter pylori in the development of gastric cancer. Method We obtained information from previously publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(109 citation statements)
references
References 102 publications
1
74
0
3
Order By: Relevance
“…The list of such diseases is wide and continues to grow, including: chronic otitis media/sinuses, endocarditis, lung infections associated with cystic fibrosis, urinary tract infections, vaginosis, osteomyelitis, chronic wound infections, catheter-related infections, and cancers of bile ducts and digestive system [ 4 , 5 , 8 ]. In the context of the last type of infections, attention should be focused strongly on spiral, Gram-negative rods colonizing the gastric mucosa— Helicobacter pylori [ 9 , 10 ].…”
Section: The Issue Of Biofilm Formation In the Biomedical Sectormentioning
confidence: 99%
“…The list of such diseases is wide and continues to grow, including: chronic otitis media/sinuses, endocarditis, lung infections associated with cystic fibrosis, urinary tract infections, vaginosis, osteomyelitis, chronic wound infections, catheter-related infections, and cancers of bile ducts and digestive system [ 4 , 5 , 8 ]. In the context of the last type of infections, attention should be focused strongly on spiral, Gram-negative rods colonizing the gastric mucosa— Helicobacter pylori [ 9 , 10 ].…”
Section: The Issue Of Biofilm Formation In the Biomedical Sectormentioning
confidence: 99%
“…Upon entering the cytoplasm of gastric epithelial cells via a “molecular syringe” typical of bacterial type IV secretion systems (T4SS), CagA undergoes tyrosine phosphorylation triggering it to act as a mitogen by activating the Ras/Raf/MAPK/ERK pathway [ 27 , 28 ] (a well-known major pro-oncogenic pathway which signals for cellular proliferation). Activation of the MAPK/ERK pathway further induces the “hummingbird” phenotype, which is characterised by an elongated shape reminiscent of epithelial mesenchymal transition (EMT) and increased cell motility [ 29 ].…”
Section: Implications Of H Pylorimentioning
confidence: 99%
“… Activation of several inflammatory pathways known to produce cytokines mediated by H. pylori infection. CagA injected via T4SS which is phosphorylated by Src activates Ras/Raf/MAPK/ERK via SHP-2 [ 27 ]; nuclear translocation of ERK subsequently induces ETS like-1 protein (ELK1) and serum response factor (SRF) binding to the serum response element (SRE) leading to transcription of AP-1 [ 28 ]. STAT3 dimerisation and nuclear translocation also occurs after CagA mediated activation of JAK.…”
Section: Figurementioning
confidence: 99%
“…Despite the inflammatory response, Helicobacter pylori is capable of evading the antibacterial immune reaction [ 26 , 27 , 28 , 29 , 30 , 31 ]. Although the significance of cagA gene and proteins for the bacterial physiology has yet to be fully elucidated [ 26 , 30 , 31 , 32 ], the cagA protein has been shown to be a marker of the cag pathogenicity island of Helicobacter pylori, and several studies have revealed that intestinal metaplasia, sporadic gastric cancer and mucosa-associated lymphoid tissue (MALT) lymphoma are most commonly found in subjects infected with cagA -positive strains [ 28 , 33 , 34 , 35 , 36 ].…”
Section: Gastric Cancer: Sporadic and Hereditary Formsmentioning
confidence: 99%